Evolution of oxytocin pathways in the brain of vertebrates - Knobloch, H. S.; Grinevich, Valery (Frontiers in Behavioral Neuroscience, 2014)
The central oxytocin system transformed tremendously during the evolution, thereby adapting to the expanding properties of species. In more basal vertebrates (paraphyletic taxon Anamnia, which includes agnathans, fish and amphibians), magnocellular neurosecretory neurons producing oxytocin, vasopressin and their homologs reside in the wall of the third ventricle of the hypothalamus composing a single hypothalamic structure, the preoptic nucleus. This nucleus further diverged in advanced vertebrates (monophyletic taxon Amniota, which includes reptiles, birds and mammals) into the paraventricular and supraoptic nuclei with accessory nuclei between them. The individual magnocellular neurons underwent a process of transformation from primitive uni- or bipolar neurons into highly differentiated neurons. Due to these microanatomical and cytological changes, the ancient release modes of oxytocin into the cerebrospinal fluid were largely replaced by vascular release. However, the most fascinating feature of the progressive transformations of the oxytocin system has been the expansion of oxytocin axonal projections to forebrain regions. In the present review we provide a background on these evolutionary advancements. Furthermore, we draw attention to the non-synaptic axonal release in small and defined brain regions with the aim to clearly distinguish this way of oxytocin action from the classical synaptic transmission on one side and from dendritic release followed by a global diffusion on the other side. Finally, we will summarize the effects of oxytocin and its homologs on pro-social reproductive behaviors in representatives of the phylogenetic tree and will propose anatomically plausible pathways of oxytocin release contributing to these behaviors in basal vertebrates and amniots.